Estimating the in-vivo HIV template switching and recombination rate. (January 2016) - Cromer, Deborah; Grimm, Andrew J.; Schlub, Timothy E.; Mak, Johnson; Davenport, Miles P.
Abstract : Background: HIV recombination has been estimated in vitro using a variety of approaches, and shows a high rate of template switching per reverse transcription event. In-vivo studies of recombination generally measure the accumulation of recombinant strains over time, and thus do not directly estimate a comparable template switching rate. Method: To examine whether the estimated in-vitro template switching rate is representative of the rate that occurs during HIV infection in vivo, we adopted a novel approach, analysing single genome sequences from early founder viruses to study the in-vivo template switching rate in the env region of HIV. Results: We estimated the in-vivo per cycle template switching rate to be between 0.5 and 1.5/1000 nt, or approximately 5–14 recombination events over the length of the HIV genome. Conclusion: The in-vivo estimated template switching rate is close to the in-vitro estimated rate found in primary T lymphocytes but not macrophages, which is consistent with the majority of HIV infection occurring in T lymphocytes. Abstract : Supplemental Digital Content is available in the text